Mustadh’afin Group in Economics According to the Qur’an - La Coy; Isman Ahadi Lebu Raya; Kamilul Himam; Ghozi Mubarok (Al-Fadilah: Islamic Economics Journal, 2024)
This study aims to explore how the Qur'an views the mustadh'afin group in the economic field and to understand the condition of the mustadh'afin. The timeless role of the Qur'an enables it to address the changes of an era that demand humans to progress, yet this overlooks the equal rights that should be given to the mustadh'afin. The economic situation of the mustadh'afin arises due to selfishness and an individualistic attitude focused solely on personal enrichment. This results in increasing economic disparity. To understand the mustadh'afin, it is necessary to study the Qur'an, which classifies the mustadh'afin into four groups: the poor, orphans, beggars, and slaves. Through this classification, the Qur'an explains the rights and freedoms that the weak should possess, emphasizing the concept of life grounded in justice and the proper management of zakat or taxes.